THE IMPORTANCE OF USING THE «FLIPPED CLASSROOM» MODEL IN THE FORMATION OF LINGUOMETHODOLOGICAL COMPETENCE OF PHILOLOGY STUDENTS - Mırzabaeva, Muxabbat Baxıtbaevna (SCIENCE and SOCIETY, 2026)
This article describes the role of linguomethodological competence in the training of future philologists in the higher education system and the importance of the innovative "Flipped Classroom" model in its development. The article analyzes the limitations of traditional teaching methods and proposes methodological approaches aimed at independent acquisition of theoretical knowledge and improvement of practical skills in the classroom.
Keywords: linguomethodical competence; Flipped Classroom; innovative education; interactive methods; pedagogical skills